Respuesta :
Answer:
The answers to the questions are;
(a) The acceleration of the first astronaut is a₁ is 1.146 × 10⁻¹¹m·s⁻²
The acceleration of the second astronaut is a₂ = 1.0347×10⁻¹¹m·s⁻²
(b) If the astronauts’ acceleration remained constant they would have to wait for 15.67 days before reaching each other.
(c) The acceleration would not remain constant but would increase as they get closer because a ∝ [tex]\frac{1}{r^2}[/tex].
Explanation:
To solve the question, we note
Firstly Newton's law of universal gravitation is given by
F₁ = F₂ = F = G×[tex]\frac{m_1*m_2}{r^2}[/tex]
Where
m₁ = Mass of the first astronaut = 65 kg
m₂ = Mass of the second astronaut = 72 kg
F₁ = Force pulling the first astronaut to the second astronaut
F₂ = Force pulling the second astronaut to the first astronaut
G = Universal gravitational constant = 6.67408 × 10⁻¹¹ m³ kg⁻¹ s⁻²
r = Distance between the two astronauts = 20 m
Therefore F = 6.67408 × 10⁻¹¹ m³ kg⁻¹ s⁻²× [tex]\frac{65 kg*72 kg}{(20 m)^2}[/tex] = 7.45 × 10⁻¹⁰m·kg·s⁻²
= 7.45 × 10⁻¹⁰ N
From Newton's second law, acceleration is directly proportional to the net force that produces it.
Therefore
F₁ = F₂ = F ∝ a
and F = m×a
For F₁ we have
F₁ = m₁×a₁ = 65 kg × a₁ = 7.45 × 10⁻¹⁰ N
a₁ = (7.45 × 10⁻¹⁰ N)/(65 kg) = 1.146 × 10⁻¹¹ N/kg = 1.146 × 10⁻¹¹ m·kg·s⁻²/kg
= 1.146 × 10⁻¹¹m·s⁻²
The acceleration of the first astronaut is a₁ = 1.146 × 10⁻¹¹m·s⁻²
The acceleration of the second astronaut is given by
For F₂ we have a₂ = (7.45 × 10⁻¹⁰ N)/(72 kg) = 1.0347×10⁻¹¹m·s⁻²
The acceleration of the second astronaut is a₂ = 1.0347×10⁻¹¹m·s⁻²
Therefore the average acceleration of the two astronauts is
[tex]a_{average} = \frac{a_1+a_2}{2}[/tex] =[tex]\frac{1.0347*10^{-11}+1.146*10^{-11}}{2}[/tex] = 1.09×10⁻¹¹m·s⁻².
(b)
Here we have from the laws of motion
v² = u² + 2×a×s
s = u·t +[tex]\frac{1}{2}[/tex]·a·t²
Where:
v = Final velocity
u = Initial velocity = u₁, u₂ = 0
a = Acceleration = a₁, a₂
s = Distance traveled = s₁, s₂
t = time
To find the time, we have
Since the astronauts will both be travelling some distance s₁ and s₂ respectively at the same time t, we have
s = u·t +[tex]\frac{1}{2}[/tex]·a·t² = 0·t +[tex]\frac{1}{2}[/tex]·a·t² = [tex]\frac{1}{2}[/tex]·a·t²
s₁ = [tex]\frac{1}{2}[/tex]·a₁·t² and s₂ = [tex]\frac{1}{2}[/tex]·a₂·t²
and s₁ + s₂ = 20.0 m
Therefore [tex]\frac{1}{2}[/tex]·a₁·t² + [tex]\frac{1}{2}[/tex]·a₂·t² = 20.0 m
⇒ [tex]\frac{1}{2}[/tex]×1.146 × 10⁻¹¹m·s⁻²×t² + [tex]\frac{1}{2}[/tex]×1.0347×10⁻¹¹m·s⁻²×t² = 20.0 m
1.09×10⁻¹¹m·s⁻²×t² = 20.0 m
t² = (20.0 m)÷(1.09×10⁻¹¹m·s⁻²) = 1834125312301 s²
t =[tex]\sqrt{1834125312301 s^2}[/tex] = 1354298.8 s
But 1 day has 86400 seconds
Therefore time = (1354298.8 s)×1 day/(86400 s) = 15.67 days
Time to reach each other = 15.67 days.
(c) The acceleration would not remain constant but would increase as they get closer.
This is because the acceleration is given by
F = m×a = G×[tex]\frac{m_1*m_2}{r^2}[/tex]
That is the acceleration is inversely proportional to the square of the distance between the two astronauts
That is a ∝ [tex]\frac{1}{r^2}[/tex]
therefore the acceleration will increase as the distance between the two astronauts decreases.
![Ver imagen oeerivona](https://us-static.z-dn.net/files/d68/8d76b7a49f2b58b72a688a50f8770635.png)